Camphor: an herbal medicine causing grand mal seizures - MacKinney, Theodore G (BMJ Case Rep, 2015)
Camphor is usually used in the USA to repel insects, but it is widely used in other countries as an herb. We report the case of a 52-year-old previously healthy Nepali man who ingested approximately 10 g of pure camphor with therapeutic intention. He developed grand mal seizures, and was evaluated in an emergency room. He failed to recall the camphor ingestion initially, and was treated with phenytoin for new-onset idiopathic seizures. Examining physicians only later found out about his camphor ingestion. Finding the cause of new-onset seizures is often challenging for emergency room physicians, internists and neurologists. In addition to other well-reported causes of secondary seizures, herbal medications and supplements must also be explored.